PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN KEGUNAAN PADA IMPLEMENTASI SAK ETAP (STUDI EMPIRIS PADA UKM DI DENPASAR UTARA) - Pradipta, Aditya; supadmi, Ni luh (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) is published with the aim to facilitate the users in applying accounting principles, which is still less appropriate when using GAAP generally accepted. SAK ETAP is expected to accommodate the needs of reporting standards on Small and Medium Enterprises (SMEs) in financial reporting that is easy, transparent, and accountable. Since the enactment of SAK ETAP, the perception of the various parties came in response to the level of effectiveness, efficiency, level of convenience and usefulness (usefulness) for the new standard so interesting to study. Samples that have been will be analyzed using multiple linear regression. The number of samples used were 100 SME units in North Denpasar. The results show that there is a positive and significant impact Perceived Ease of Use and Usefulness at SAK ETAP implementation. Results of this study are expected to provide further information to investigators about the perception in the implementation of ETAP SAK.
Keywords: Perceived Ease of Use, Perceived Usefulness, SAK ETAP, SMEs